2020
DOI: 10.1186/s13584-019-0359-8
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic status, self-rated health and mental health: the mediation effect of social participation on early-late midlife and older adults

Abstract: Background: Socioeconomic status (SES) is a major determinant of diverse health outcomes, among these are selfrated-health and mental health. Yet the mechanisms underlying the SES-health relation are not fully explored. Socioeconomic inequalities in health and mental health may form along several pathways. One is social participation which is linked to better self-rated-health and mental health. We examined (1) whether various social participation practices, including the usage of information and communication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
29
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 54 publications
2
29
0
1
Order By: Relevance
“…These beliefs might moderate the stress associated with unemployment. In line with this assumption, trust has been previously studied as a moderator in the unemployment-well-being link [ 51 ], as a mediator in the SES–PD link [ 52 ], and as a moderator in the poverty-loneliness link [ 53 ]. Given the harsh restrictions on social gatherings and activities (the structural component of social capital) and the lockdown imposed during the month of April, we thought that the cognitive component would be more appropriate than the structural one for measuring social capital.…”
Section: Introductionmentioning
confidence: 99%
“…These beliefs might moderate the stress associated with unemployment. In line with this assumption, trust has been previously studied as a moderator in the unemployment-well-being link [ 51 ], as a mediator in the SES–PD link [ 52 ], and as a moderator in the poverty-loneliness link [ 53 ]. Given the harsh restrictions on social gatherings and activities (the structural component of social capital) and the lockdown imposed during the month of April, we thought that the cognitive component would be more appropriate than the structural one for measuring social capital.…”
Section: Introductionmentioning
confidence: 99%
“…Social participation can be defined as participation and involvement in social or community activities that provide interactions with others in the community and a platform for fulfilling an individual's needs for the social integration necessary for wellbeing (Levasseur et al, 2010;Dai et al, 2013;Achdut and Sarid, 2020). Social participation is beneficial for mental health (Sun and Lyu, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…One study found that social participation could explain approximately 11% of psychological health disparity among rural-urban migrants (Sun and Lyu, 2020). Previous studies revealed that social participation mediates the relationship between individual resources and mental health (Dai et al, 2013;Achdut and Sarid, 2020;Sun and Lyu, 2020). However, much evidence for the level of social participation and its association with mental health are in older adults (Kim, 2019;Wang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A number of recent studies have demonstrated that socioeconomic status (SES) is the most decisive factor affecting health [ 4 6 ]. A relation exists between prevalence of diabetes and relatively disadvantaged socioeconomic position in developing and developed countries [ 7 ].…”
Section: Introductionmentioning
confidence: 99%